Engaging health system, service and consumer representatives in the co-design of a multi-criteria decision-making framework for commissioning overweight and obesity programs and services - Laura Thomas; Suzanne Robinson; Sharyn Burns; Helen Mitchell; Andrea Begley (Health Research Policy and Systems)
Abstract Background Obesity is a multi-faceted problem that requires complex health system responses. While no single program or service is sufficient to meet every individual’s needs, some criteria that increase the likelihood of program/service quality delivery to produce effective outcomes exist. However, although research on health commissioning is available internationally and is growing within the Australian context, no evidence exists of a multi-criteria decision-making framework to address the complexity required for effective commissioning of overweight and obesity early intervention and weight management programs or services. This study aimed to develop a set of criteria to support effective commissioning in this context. Methods A mixed-methods co-design approach was used to develop a multi-criteria framework. A literature review informed a three-stage co-design consensus-gathering approach. Participants included Western Australian stakeholders from the Western Australian health system, services and consumers, who reviewed, ranked and validated responses and criteria through ongoing discussions. A deliberative forum was held between the two online, modified Delphi surveys to reach a consensus among stakeholders. Results Through the co-design, a total of 63 stakeholders were identified: 24 completed the round 1 Delphi survey assessing 22 proposed criteria, 40 attended the deliberative forum and 30 completed the round 2 Delphi survey. A total of 4 themes arose from the co-design process: (1) reduce duplication, (2) demote criteria, (3) re-organize criteria and (4) simplify language, and 10 criteria were established: safety, collaboration and consultation, appropriateness, effectiveness, efficiency, equity, evidence-based, health service delivery model, sustainability and workforce capacity and competence. The criteria were underpinned by indicators highlighting relevant sub-themes. Conclusions A multi-criteria framework was developed and its application to the commissioning process will enable the selection of programs and services that will likely have an impact on individuals’ use of and satisfaction with programs and services, overweight and obesity-related outcomes and inter-agency collaborations to maximize economic and workforce resources.